Further Excavations of Cairns at Poltalloch, Argyll - Craw, John Hewat (Proceedings of the Society of Antiquaries of Scotland, 1931)
An account of excavations three cairns. Nether Largie North Cairn contained a single cist just north of centre with carvings of cup marks and axeheads, the latter rare in Scotland. The cist contained charcoal, ochre and a human molar. Carnasserie Cairn covered a semi-circle of boulders and a cist containing a Food Vessel, charcoal and ochre. The bell cairn at Ballymeanoch was badly disturbed. Two cists were visible and the larger contained parts of a Beaker and human teeth.